Necrology of an extirpator of idolatries: Pablo Joseph de Arriaga. Original document from the Roman Archive of the Society of Jesus - Chávez, Fabiola (2007)
This paper presents a paleographic transcription of two original documents of the Archivum Romanum Societat Jesu (ARSI) in Rome, referred to the death of Jesuit Priest Pablo Joseph de Arriaga in a province of Peru. The first document has been extracted from the section called Fondo Gesuita: Elogia Defunctorum (1621-1622, 1623). Busta 115, III, 3. The second document is part of the Peru section, volume Peru 21: Vida de los difuntos desta Prov. a del Peru (Life of the Dead in this Province of Peru). 2. a. Via Citanse en carta n. 22, written in Italian of the XVII century.